Antibacterial mechanism of areca nut essential oils against Streptococcus mutans by targeting the biofilm and the cell membrane - Liu, Shuwei; Zhang, Tiantian; Li, Zhijin; Wang, Yan; Liu, Lei; Song, Zhenbo (Frontiers in Cellular and Infection Microbiology, 2023)
Dental caries is one of the most common and costly biofilm-dependent oral diseases in the world. Streptococcus mutans is the major cariogenic pathogen of dental caries. S. mutans synthesizes extracellular polysaccharides by autologous glucosyltransferases, which then promotes bacterial adhesion and cariogenic biofilm formation. The S. mutans biofilm is the principal target for caries treatment. Areca nut is a popular masticatory product in South and Southeast Asia, and also a type of herbal medicine widely used in southern China, having broad biological activity. This study was designed to explore the antibacterial activity and mechanisms of areca nut essential oil (ANEO) against S. mutans. The ANEOs separated at different temperatures exhibited different levels of antibacterial activity against S. mutans, and the ANEO separated at 70 ℃ showed the most prominent bacteriostatic activity. Anti-biofilm experiments showed that the ANEOs attenuated the adhesion ability of S. mutans by decreasing the surface hydrophobicity of the bacteria, prevented S. mutans biofilm formation by inhibiting glucosyltransferase activity, reducing extracellular polysaccharide synthesis, and reducing the total biofilm biomass and activity. Scanning electron microscopy further demonstrated the destructive effects of the ANEOs on the S. mutans biofilm. Cell membrane-related experiments indicated that the ANEOs destroyed the integrity of the cell membrane, resulting in the leakage of lactic dehydrogenase and nucleic acids. Propidium iodide staining also showed the destructive effect of ANEOs on the cell membrane. Scanning electron microscopy imaging of S. mutans cell showed the disruption of the cellular morphology by the ANEOs. In addition, the cytotoxicity assay suggested that ANEO was non-toxic towards normal oral epithelial cells. All of these results confirmed that ANEOs exerted antibacterial activity against S. mutans primarily by affecting the biofilm and disrupting the integrity of the cell membrane. Overall, EO-70 was enriched This is a provisional file, not the final typeset article in more active substances against S. mutans and has the potential to be developed as an antibacterial agent for preventing dental caries. Additionally, this study presents a new method for the separation of essential oil components.